2020
DOI: 10.1155/2020/5743972
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Galvanic Vestibular Stimulation Modified the Neuronal Potential in the Vestibular Nucleus

Abstract: Vestibular nucleus (VN) and cerebellar flocculus are known as the core candidates for the neuroplasticity of vestibular system. However, it has been still elusive how to induce the artificial neuroplasticity, especially caused by an electrical stimulation, and assess the neuronal information related with the plasticity. To understand the electrically induced neuroplasticity, the neuronal potentials in VN responding to the repeated electrical stimuli were examined. Galvanic vestibular stimulation (GVS) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…To date, however, only a handful of in-vivo studies have investigated how GVS alters signal transmission in central vestibular pathways. One 2020 study assessing how vestibular nuclei neurons encode combined GVS and motion stimulation [45] reported that sub additive responses similar to those reported for the integration of semicircular canal and otolith afferents in these cells [46]. This same group also reported that repeated GVS reduces vestibular nuclei neuronal potentials [45].…”
Section: Effects Of Galvanic Vestibular Stimulation On the Central Ve...mentioning
confidence: 82%
See 1 more Smart Citation
“…To date, however, only a handful of in-vivo studies have investigated how GVS alters signal transmission in central vestibular pathways. One 2020 study assessing how vestibular nuclei neurons encode combined GVS and motion stimulation [45] reported that sub additive responses similar to those reported for the integration of semicircular canal and otolith afferents in these cells [46]. This same group also reported that repeated GVS reduces vestibular nuclei neuronal potentials [45].…”
Section: Effects Of Galvanic Vestibular Stimulation On the Central Ve...mentioning
confidence: 82%
“…One 2020 study assessing how vestibular nuclei neurons encode combined GVS and motion stimulation [45] reported that sub additive responses similar to those reported for the integration of semicircular canal and otolith afferents in these cells [46]. This same group also reported that repeated GVS reduces vestibular nuclei neuronal potentials [45]. Notably, this reduction was accompanied by a decrease in AMPA and NMDA receptors, leading to proposal that GVS induces a reduction in the number of glutamate receptors that in turn modifies neuronal potentials in the vestibular nucleus.…”
Section: Galvanic Vestibular Stimulationmentioning
confidence: 99%
“…The extracellular neural recording in the vestibular nucleus (VN) was performed based on our previous studies 25 , 14 , 20 . The neural recording was initiated by defining a center on the skull.…”
Section: Methodsmentioning
confidence: 99%
“…Vestibular system is a highly plastic system, and its plastic mediation is built by the molecular and cellular modification [14][15][16][17] . The modified responses are mainly regulated by various types of neurotransmitters, and the glutamate is one of excitatory neurotransmitters, which is known as the most abundant amino acid in the brain 18,19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation